The relationship between safety training and safety communication torards behaviour among employees in GC - Nur Maisarah, Hashim (2024)
Safety training and safety communication are an important element to shape employee behaviour directly or in directly at the factory. This study aimed to study the relationship between safety training and safety communication towards safety behaviour among employees in the manufacturing company which is GC. A self-administrative questionnaire was applied for data collection which involved 138 respondents. Raw data collection process was analyzed by using Statistical Package for the Social Science (SPSS) Version 26.0 specifically for descriptive and inferential analysis. The progression exploration revealed that safety training and safety communication has a positive significant relationship towards the dependent variables which are safety behavior. Correlation analysis revealed that there is a positive correlated relationship. While regression analysis shows that the R-squared value is 0.176. The impact showed that GC should provide more training and communicate more often such as provide program related to safety issue in the factory. All employees work in the factory need to comply and work together to reduce the number of accidents. Comprehensively, this study may provide guidance to factory in order to provide better training and ensure there is effective communication related to safety in their workplace.